Semiotic Analysis Of The Message Of Tolerance In The Film "Ajari Aku Islam" Charles Sanders Pierce Method (International Journal of Cultural and Social Science, 2022)
This study aims to find out what the meaning of the sign of tolerance and Islamic values ??in the film "Ajari Aku Islam" is. This research is a qualitative descriptive study. Data collection techniques using observation and documentation using the semiotic approach of Charles Sanders Pierce. The author is interested in using this semiotic theory to deepen the working pattern of the triangle meaning described in the Triadic and Trichotomy analysis to answer the formulation of the problem in the research. Pierce's semiotics uses the term representamen as a form of initial sign, then object as a sign reference, and interpretant as meaning. The object of research is the film "Teach Me Islam". This research then produces the meanings of religious tolerance and Islamic values ??which are seen in the film "Ajari Aku Islam". The conclusions of this study include the meaning of religious tolerance which is shown through 4 principles, namely respecting the differences in the beliefs of others, giving freedom in choosing religion, understanding mutual understanding between religions and not looking at physical and psychological differences in socializing. The Islamic values ??in the film "Ajari Aku Islam" include; human relationship with God, human relationship with oneself, human relationship with fellow human beings.